2022
DOI: 10.1063/5.0096986
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation bubble collapse in a vicinity of a rigid wall with a gas entrapping hole

Abstract: This paper aims to reveal the influence of a rigid wall with a gas entrapping hole on the characteristics of the dynamic behavior of a laser-induced bubble collapse. A high-speed camera system was used to record the oscillation process of the laser-induced bubble on a rigid wall with a gas entrapping hole. When a bubble is generated by a laser above the wall with a gas entrapping hole, the entire bubble collapse stays away from the wall or splits into two bubbles because of a radial jet induced by bubble contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Table 1 shows the target parameters of the study model. Table 2 shows a description of the cavitation criteria and associated parameters that may be relevant in this article [12][13][14][15][16][17][18]. • NPSH3: The cavitation allowance tested by the double suction centrifugal pump when the head drops by 3%.…”
Section: 1. Experimental Designmentioning
confidence: 99%
“…Table 1 shows the target parameters of the study model. Table 2 shows a description of the cavitation criteria and associated parameters that may be relevant in this article [12][13][14][15][16][17][18]. • NPSH3: The cavitation allowance tested by the double suction centrifugal pump when the head drops by 3%.…”
Section: 1. Experimental Designmentioning
confidence: 99%
“…Similarly, Sun et al. (2022 b ) investigated bubble collapse near a rigid surface with a gas-entrapping hole. This concept was also investigated by Gonzalez-Avila et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has investigated the problem of a plate with a through-hole bounding a free surface in relation to breaches of maritime hulls (Cui et al 2021(Cui et al , 2022He et al 2021). Similarly, Sun et al (2022b) investigated bubble collapse near a rigid surface with a gas-entrapping hole. This concept was also investigated by Gonzalez-Avila et al (2020) and Sun et al (2022a), who considered surfaces with a pattern of gas-entrapping holes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found that near the water–air free interface or bubbles, cavitation bubbles can generate jets away from the interface or bubbles [14] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . Gonzalez et al [32] fabricated mushroom-shaped microcavities on SiO2/Si substrates, which can effectively capture air underwater.…”
Section: Introductionmentioning
confidence: 99%
“…The potential flow model theory validates this assumption and reproduces the repellent effect of the surface on cavitation bubbles. Sun et al [33] studied the different dynamic characteristics of cavitation bubble collapse near a rigid wall with a gas-entrapping hole. There are two modes of cavitation bubbles near the wall with a gas entrapping hole, which are moving away from the wall and splitting into two bubbles, depending on the distance between the wall and the bubble.…”
Section: Introductionmentioning
confidence: 99%